Vestervang at Kirke Hyllinge, Zealand - Ole Thirup Kastholm (Danish Journal of Archaeology, 2012)
In 2007 Roskilde Museum investigated a settlement dated to the late Germanic Iron Age/Viking Age. The excavated area of c. 18,000 m2 unveiled 18 longhouses and 21 pit houses but is probably best understood as a single farm in c. six phases. The settlement consists of rather modest structures, not exceeding 20 m in length, which contrasts with the broad range of rich contemporary metal stray finds from the site. This paper presents the excavation results and briefly proposes a possible connection between this site and the nearby elite complex of Lejre.